2021
DOI: 10.3390/f12060751
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intra-Continental Genetic Variation in the Generalist Conifer Wood Saprobic Fungus Phlebiopsis gigantea

Abstract: Phlebiopsis gigantea (Fr.) Jülich is a well-known generalist conifer wood saprobe and a biocontrol fungus used in several world countries to prevent stump infection by tree pathogenic Heterobasidion fungal species. Previous studies have reported the presence of regional and continental genetic differentiation in host-specific fungi, but the presence of such differentiation for generalist wood saprobes such as P. gigantea has not been often studied or demonstrated. Additionally, little information exists on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…However, P. gigantea products, such as the Rotstop ® C formulation (BioFOrest Tehnologies Inc., Sault Ste. Marie, Canada) that is commercially available in the US, are based on an eastern strain of P. gigantea, are genetically distinct from western strains of the same fungus and recent work has argued against deploying them in western US forests [47]. Our study was the first to apply and report the efficacy of California isolates of P. gigantea in terms of preventing H. occidentale establishment or growth on stumps and is thus extremely timely and provides data on a possible future alternative to the commercially available P. gigantea formulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, P. gigantea products, such as the Rotstop ® C formulation (BioFOrest Tehnologies Inc., Sault Ste. Marie, Canada) that is commercially available in the US, are based on an eastern strain of P. gigantea, are genetically distinct from western strains of the same fungus and recent work has argued against deploying them in western US forests [47]. Our study was the first to apply and report the efficacy of California isolates of P. gigantea in terms of preventing H. occidentale establishment or growth on stumps and is thus extremely timely and provides data on a possible future alternative to the commercially available P. gigantea formulation.…”
Section: Discussionmentioning
confidence: 99%
“…stumps [ 20 ]. A recent study identified three genetically differentiated lineages within P. gigantea , one from Europe, one from eastern North America and one from California [ 21 ]. However, there is no information on whether intraspecific variation between sympatric populations of the fungus associated with different hosts may occur.…”
Section: Introductionmentioning
confidence: 99%
“…(Bailey et al., 2003; Holdenrieder & Greig, 1998; Korhonen et al., 1994). In commercial forestry operations, P. gigantea is now widely used in Europe and North America with strains patented as Rotstop® (Dovana et al., 2021; Gonthier & Thor, 2013). The primary mode of action of P. gigantea involves resource competition and the ability to quickly colonize stumps (Holdenrieder & Greig, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…(Bailey et al, 2003;Holdenrieder & Greig, 1998;Korhonen et al, 1994). In commercial forestry operations, P. gigantea is now widely used in Europe and North America with strains patented as Rotstop® (Dovana et al, 2021;Gonthier & Thor, 2013).…”
Section: Introductionmentioning
confidence: 99%